The Influence of Investment Opportunity Set, Leverage, and Profitability on Earnings Management with Audit Quality as a Moderating Variable (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period of 2018-2022) - Christiningrum, Christiningrum; Vira P. Pinasti, Brigita (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine whether investment opportunity set (IOS), leverage, and profitability influence earnings management practices with audit quality as a moderating variable. Earnings management is measured using discretionary accruals (DA) which was calculated using the Modified Jones Model. IOS used market value to book value of assets (MVBA), while leverage used debt-to-equity ratio (DER), and profitability used return on assets (ROA) as their proxies, respectively. This research used 36 manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2022 as its sample. The findings show that investment opportunity set and profitability have a significantly positive impact on earnings management practices, with a significance level of ?=1%. Meanwhile, leverage does not affect earnings management practices. The results further indicate that audit quality can moderate the impact of the investment opportunity set and profitability on earnings management practices. This highlights that the investment opportunity set and profitability significantly influence earnings management practices while audit quality can moderate their impact.